중학생의 일기변화 관련 개념 지식상태와 교수-학습 효과 - 윤마병; Ma Byong Yoon (과학교육연구지, 2011)
This study developed examination test tools for concepts of weather changes of middle school students, analyzed the hierarchy of concepts associated with weather changes by means of knowledge state analysis method, and examined the knowledge state and lesson effects of each individual learner. The hierarchy of the knowledge state of concepts of middle school students associated with weather changes followed the steps of ``humidity → air mass → cloud → precipitation → front → weather`. Cases were identified where the knowledge state of students that was thought to be similar to each other among the group of students who have scored almost the same points and thus were thought to have almost the same learning ability, have turned out different in the knowledge state from each other. Namely, the level of knowledge state structuralized differed, suggesting that differing prescriptions should be made according to the knowledge state of each student concerned. Analysis of the knowledge state of learners helps prepare learning prescriptions for each student and appraise prior learning. To examine effects of teaching-learning that has taken into consideration the hierarchy of knowledge state and concepts, lessons were conducted in comparison with the order in which syllabuses are presented in the textbooks, with the result that when knowledge state of learners have been taken into consideration, students made scores significantly higher (p < .05) than otherwise. This indicates that in introducing the unit of weather changes better teaching and learning can be achieved by reordering the contents of subject matters of the textbook by grasping the knowledge state of learners.